1988
DOI: 10.1007/bf02372309
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoid-host relationship betweenTrioxys (Binodoxys) Indicus [Hymenoptera: Aphidiidae] andAphis Craccivora [Hemiptera: Aphididae]. VI. Impact of males on the number of progeny of the parasitoid reared on certain host plants

Abstract: The present paper elucidates the impact of males on the reproductive rate of Trioxys (Binodoxys) indicus reared on the aphids of Cajanus cajan, Dolichos lablab and Solanum melongena host plants. The F~ offspring increases with the increase of parasitoid number. This increase is maximum in C. cajan followed by D. lablab and S. melongena reared aphids. The presence of male parasitoids caused a significant decrease in the emergence of F~ generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This is known to occur e.g. among parasitoids (Kfir et al, 1975;Singh & Sinha, 1982;Kumar et al, 1988).…”
mentioning
confidence: 99%
“…This is known to occur e.g. among parasitoids (Kfir et al, 1975;Singh & Sinha, 1982;Kumar et al, 1988).…”
mentioning
confidence: 99%
“…With the increase of parasitoid density the number of emerging offspring increases upto four parasitoids, then shows a tendency towards stabilisation. This indicates that in order to achieve a considerable number of parasitoids, more parasitoids might be required Pandey et al 1986;Kumar et al 1988;Abidi et al, 1989;Hagvar & Hofsvang, 1990). Table 1 and Fig 1 show that when double the number of parasitoids were put in for parasitisation, a doubling of parasitisation ratio in any case was not observed which might be due to limited oviposition time (Cloutier, 1984;Kumar & Tripathi, 1985Pandey et al, 1986;Kumar et al, 1988;Abidi et al, 1989) and the reduction of individual's efficiency because of mutual interference (Lawrence, 1981;Avilla & Albajes, 1983;Kumar & Tripathi, 1985;Kumar et al, 1988).…”
Section: Resultsmentioning
confidence: 96%
“…This indicates that in order to achieve a considerable number of parasitoids, more parasitoids might be required Pandey et al 1986;Kumar et al 1988;Abidi et al, 1989;Hagvar & Hofsvang, 1990). Table 1 and Fig 1 show that when double the number of parasitoids were put in for parasitisation, a doubling of parasitisation ratio in any case was not observed which might be due to limited oviposition time (Cloutier, 1984;Kumar & Tripathi, 1985Pandey et al, 1986;Kumar et al, 1988;Abidi et al, 1989) and the reduction of individual's efficiency because of mutual interference (Lawrence, 1981;Avilla & Albajes, 1983;Kumar & Tripathi, 1985;Kumar et al, 1988). Under field conditions a strong mutual interference might be taking place due to an increase in the parasitoid density which may result in the dispersal of the parasitoid Abidi et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that when host density increased both the leaf arrival time and the host arrival time reduced, but that stinging and mummies increased. According to Brown et al (1970), the increased concentrations of kairomones that promote parasitoid activity may be to blame, or the increased surface area of interaction between the hosts, according to Kumar (1988) and Saleh (2008).…”
Section: Discussionmentioning
confidence: 99%